Papillary lesions of the canine mammary gland: description and casuistry - M.C. Flecher; F. R. Souza; N.M. Avelar; T.C.M. Lopes; K.Y. R. Nakagaki; G.D. Cassali (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The purpose of the study was to identify the casuistry of papillary mammary neoplasms in female dogs, describe their epidemiological (age, breed) and morphological characteristics, and determine the survival of patients. Overall survival was estimated using Kaplan-Meier curves and comparisons between groups were performed using the Cox Mantel log-rank test (p < 0.05 were considered significant). A study was carried out between 2005 and 2020 at the Laboratory of Comparative Pathology of the Institute of Biological Sciences of the Federal University of Minas Gerais. The study identified 288 female dogs with 353 papillary neoplasms, 36.93% benign (papilloma, sclerosing papilloma, and papilloma with carcinomatous areas in situ) and 63.06% malignant (non-invasive papillary carcinoma, invasive papillary carcinoma, invasive papillary carcinomas with micropapillary areas and micropapillary areas in situ, and solid papillary carcinoma). Papilloma (53.1%) and invasive papillary carcinoma (46.64%) were the most frequent. Most papillary neoplasms were smaller than 3.0 cm in size and presented no metastases in lymph nodes and no distant metastases. However, the invasive papillary carcinomas’ average size was larger than the papillomas and non-invasive carcinomas. Papillary neoplasms are often associated with other types of mammary neoplasms; thus the survival of most female dogs is difficult to determine.